Eviction, Gatekeeping and Militant Care: Moral Economies of Housing in Austerity London. Issue 1 (1st January 2022) - Wilde, Matt
ABSTRACT: This article uses the lens of moral economies to examine the everyday experience of eviction, precarious housing and grassroots activism in contemporary London. Situated within a context of ongoing austerity measures, it explores how divergent, conflicting and overlapping moral economies of housing emerge both within the state and at its margins, as local authorities struggle to reconcile contradictory obligations to both uphold property relations and offer a duty of care to tenants. The article shows how being precariously housed is experienced as a series of disorientating advice and support encounters in which the right to state assistance is contested by low-income tenants, state housing officers and community activists. It contends that these encounters are surface-level expressions of a deeper underlying struggle over the political and moral status of housing, in which the unresolved tension between housing as a home and housing as a commodity shapes contested visions of economic justice.